Comparative Effect of Different Phosphatic Fertilizers on Growth of Rapeseed (Brassica napus L.) in Alkaline Calcareous Saline-Sodic Soils. Issue 20 (13th November 2021) - Sabir, Muhammad; Sultan, Tariq; Yaseen, Muhammad; Ahmad, Riaz; Tarar, Zahid Hassan
ABSTRACT: Phosphorus (P) deficiency is an important nutritional constraint for crop productivity in alkaline-calcareous saline-sodic soils. Generally, farmers apply different P fertilizers to overcome P deficiency; however, different P fertilizers may have different efficiency in saline-sodic and normal soils. An experiment was conducted to investigate the comparative effect of phosphatic fertilizers, viz . single super phosphate (SSP), di-ammonium phosphate (DAP) and triple superphosphate (TSP), on the growth of rapeseed. These fertilizers were applied to three different types of soils, viz . normal, saline-sodic soil-I {EC, 7 dS m −1 ; SAR, 25 (mmol L −1 ) 1/2 } and saline-sodic soil-II {EC, 14 dS m −1 ; SAR, 50 (mmol L −1 ) 1/2 ). In normal soil, DAP was effective to enhance growth compared to other fertilizers. In saline-sodic soil-I, SSP enhanced shoot dry weight (SDW) to the maximum (51%) compared to control and by 12% and 21% compared to TSP and DAP, respectively. In saline-sodic-II, SSP increased SDW by 51% compared to control and by 14% and 20% compared to TSP and DAP, respectively. In saline-sodic soil-I, SSP-fertilized plants had 22% and 7% higher membrane stability index compared to plants grown with DAP and TSP. In saline-sodic soil-I and II, plants grown in pots fertilized with SSP accumulated the maximum chlorophyll contents, while control plants contained the minimum. In saline-sodic soils, SSP increased P concentration in shoot and Olsen P compared to other fertilizers. It is concluded that SSP is relatively more effective and improves plant growth in saline-sodic soils, while DAP is suitable for normal soils.